RELEVANSI NILAI LABA, NILAI BUKU DAN ARUS KAS BERSIH PADA PERUSAHAAN FOOD AND BEVERAGE DI INDONESIA - Oktaviana, Ulfi Kartika (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
Investment through the capital market, particularly in the form of shares in addition to promising results are also risky. This is becouse the stock price is volatile and unpredictable. Stock price are influenced by many factors stemming from internal and external compinies. Company performance factor s was important information for investors to make good decision. This study aims to investigate value relevance of accounting information (earning per share, book value and cash flow). Better quality will increase value relevance of earning, book value and cash flow . Using financial data of food and beverage companies listed in Jakarta Stock Exchage from periode 2007 to 2009. The study find that stock price is influenced by earning, book value and cash flow. Earning, book value and cash flow s influence appear to be value relevant. nvestment through the capital market, particularly in the form of shares in addition to promising results are also risky. This is becouse the stock price is volatile and unpredictable. Stock price are influenced by many factors stemming from internal and external compinies. Company performance factor s was important information for investors to make good decision. This study aims to investigate value relevance of accounting information (earning per share, book value and cash flow). Better quality will increase value relevance of earning, book value and cash flow . Using financial data of food and beverage companies listed in Jakarta Stock Exchage from periode 2007 to 2009. The study find that stock price is influenced by earning, book value and cash flow. Earning, book value and cash flow s influence appear to be value relevant. Keywords: value relevance, earnings, book value, cash flow Investment through the capital market, particularly in the form of shares in addition to promising results are also risky. This is becouse the stock price is volatile and unpredictable. Stock price are influenced by many factors stemming from internal and external compinies. Company performance factor s was important information for investors to make good decision. This study aims to investigate value relevance of accounting information (earning per share, book value and cash flow). Better quality will increase value relevance of earning, book value and cash flow . Using financial data of food and beverage companies listed in Jakarta Stock Exchage from periode 2007 to 2009. The study find that stock price is influenced by earning, book value and cash flow. Earning, book value and cash flow s influence appear to be value relevant. Keywords: value relevance, earnings, book value, cash flow